2018
DOI: 10.3390/polym10101063
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled, Adjuvant/Antigen-Based Nanovaccine Mediates Anti-Tumor Immune Response against Melanoma Tumor

Abstract: Malignant melanoma is a highly aggressive type of cancer that requires radical treatment strategies to inhibit the cancer cell progression and metastasis. In recent years, preclinical research and clinical trials on melanoma treatment have been considerably focused on the adjuvant-based immunotherapy for enhancing the immune response of innate immune cells against cancer cells. However, the clinical outcome of these adjuvant-based treatments is inadequate due to an improper delivery system for these immune act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Splenocytes were isolated from mice that showed complete regression of distant tumors. Effector T cells were prepared and purified using a nylon column method as previously described. , Collected effector T cells were labeled with 2 μM carboxyfluorescein succinimidyl ester (CFSE) (BioLegend) for 5 min at room temperature. CT26 cells were labeled with CellTracker Red CMTPX dye (Invitrogen) at room temperature and then cocultured with CFSE-labeled T cells in a 24-well plate at a T cell:target cell ratio of 100:1.…”
Section: Methodsmentioning
confidence: 99%
“…Splenocytes were isolated from mice that showed complete regression of distant tumors. Effector T cells were prepared and purified using a nylon column method as previously described. , Collected effector T cells were labeled with 2 μM carboxyfluorescein succinimidyl ester (CFSE) (BioLegend) for 5 min at room temperature. CT26 cells were labeled with CellTracker Red CMTPX dye (Invitrogen) at room temperature and then cocultured with CFSE-labeled T cells in a 24-well plate at a T cell:target cell ratio of 100:1.…”
Section: Methodsmentioning
confidence: 99%
“…This enhanced permeability and retention (EPR) principle is one of the key concepts for cancer nanotechnology; carriers with a hydrodynamic diameter larger than ∼20 nm avoid rapid kidney filtration, and carriers smaller than the tumor-dependent interendothelial spacing can extravasate into the tumor tissue. , Thus, polymeric carriers for solid tumors have generally been designed to have hydrophilic shielding and range in size between 20 and 200 nm in diameter . These design principles have been applied to polymeric formulations for tumor delivery of peptides in murine cancer models. ,, However, the broad relevance of EPR-based tumor delivery for clinical nanomedicines is the subject of significant discussion and debate. , Many nanomedicines that perform well in animal models have not translated to clinical success . A broad analysis of tumor accumulation by nanoparticle formulations revealed that a median 0.7% injected dose is delivered to the solid tumor across varying materials, size, charge, and tumor models .…”
Section: Rational Design Of Polymeric Carriers For Improved Peptide D...mentioning
confidence: 99%
“…In another vaccine system, Rajendrakumar et al . formulated nanocomplexes containing poly­(sorbitol)- co -PEI (PSPEI) complexed with tumor lysate protein and adjuvant poly I:C (PSPEI–PAA) . In a B16F10 subcutaneous model, PSPEI–PAA showed high DC uptake in lymph nodes and increased tumor infiltration by CTLs.…”
Section: Rational Design Of Polymeric Carriers For Improved Peptide D...mentioning
confidence: 99%
“…The development of biomimetic NPs with chemical and structural modifications to mimic the biological environment is an established approach for cancer therapy. Nanovaccines are novel platforms for delivery of both adjuvants and antigens that generate a strong antitumor response by modulating the immune system [124]. Various type of nanovaccines, such as liposomes, protein NPs, and cell-membrane-coated nanomicelles, have been recently developed for successful anti-cancer therapy [125,126].…”
Section: Applications Of Biomimetic Nanovaccinesmentioning
confidence: 99%